VOZES TRANSGRESSORAS: agentes, mediações culturais, agenciamentos e América Latina nas páginas do jornal Lampião da Esquina (1978-1981) - GEISELLY MARCAL DA SILVA (2022)
Interpreted through the lens of heteronormative oppressive hegemonic culture as depraved, promiscuous, unhealthy and perverted, the LGBTQQICAPF2K+ population undergoes different treatments in Brazilian society, marked above all by the brutality of the violence imposed on these agents. This Final paper is the result of a bibliographical research with a descriptive qualitative approach, entitled “Agents, cultural mediations, assemblages, and Latin America in the pages of the newspaper Lampião da Esquina (1978-1981). The newspaper as a cultural artifact through its contents acts as a producer of subjects by promoting teachings through cultural pedagogies. The study also outlines the oppositional alternative press newspaper that brings a debate about difference to Brazil from a decolonial perspective in a Brazil of openness in which difference is emerging since the coloniality of the power of authoritarian regimes it is also expressed in the markers of difference in Latin America as a whole. After all, what is the place of homosexuality within political agendas? What is the place of women? What is the indigenous space? What is the place of ethnic-racial issues? There is also an analysis of the construction of meanings and practices of subversion in the pages of the newspaper Lampião da Esquina on homosexuality’s/transgressive sexualities in Latin America when discussing the gay issue of Latin American authoritarian regimes. For the theoretical foundation of the work, this study is reported through the lens of Cultural Studies and a dialogue is made with several authors, such as: Jesus Martín Barbero (2015); Gayatri Chakravorti Spivak (2010) in addition to the constructs of Bernardo Kucinski (2001); Renan Quinalha (2021); Viviane Camozzato (2015); Douglas Kellner (2001); Elisabeth Ellsworth (2001); Marlécio Maknamara (2020); Patricia Hill Collins (2021). This look from the margin of the non-hegemonic press and its due engagement crystallizes guidelines for struggles for rights in the construction of reflections and knowledge of agents when questioning the dominant heterosexual, white, Christian, normative, patriarchal and sexist in the authoritarian context. Keywords: Lampião da Esquina; Cultural Studies; Agency; Cultural pedagogy; Alternative press.